Perception, practices towards research and predictors of research career among UG medical students from coastal South India: A cross-sectional study - Harsha Kumar H; Jayaram S; Kumar Ganesh; Vinita J; Rohit S; Satish M; Shusruth K; Nitin; Akhilesh (Wolters Kluwer Medknow Publications, 2009)
Background : The number of physician scientists worldwide is decreasing. A review of literature suggests paucity of information examining perceptions and practices towards research among medical undergraduate students in India. Hence, this study was undertaken. Objectives : To understand (a) the awareness, skills, perceptions and practices among undergraduate (UG) medical students towards research, (b) the factors responsible for willingness to take up research as a career among the undergraduates. Material and Methods : This is a questionnaire-based qualitative study. This study was conducted in Kasturba Medical College, Mangalore. A pre-tested questionnaire examining their awareness, perceptions and practices towards research in medical field was used. Consent was obtained from the Dean of the College and student participation was voluntary. Analysis : The information was analyzed using SPSS version 11. Univariate and Multivariate analyses were done to know the willingness to consider research as a career. Results : A total of 471 students responded giving a response rate of 55.41%. Nearly 70% were aware about research though their level of awareness varied. Various skills of conducting research were known to 47% of the students. Most (76%) were part of a research team mainly as a part of the medical curriculum, a few (8.3%) were confident of research as a career option. The multivariate reveals that those with good skill and students who involved in research in addition to curriculum were more likely to take up research as career option/would continue to do research in future. Conclusions : Good training and student support programs exclusively for research would motivate students to opt for research careers.